2012
DOI: 10.1093/jat/bks064
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity of Tapentadol Specimens with DRI Methadone Enzyme Immunoassay

Abstract: A substantial incidence of positive methadone screens for pain management urine specimens using a commercial enzyme immunoassay (EIA) was observed in the absence of a methadone prescription, with negative methadone confirmation by ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS-MS). Tapentadol was the only common prescription among the investigated specimens. Tapentadol or one of its three major metabolites was tested at various concentrations (100-200,000 ng/mL) against the DRI EIAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Poppy seed containing foods 1,2,18,48 , some fluoroquinolone antibiotics (levofloxacin 49 , ofloxacin 49 ), imipramine 46 , naltrexone 46 , naloxone 50 , rifampin/rifampicin 51 53 , verapamil 54 , verapamil metabolites 54 , quetiapine 55,56 , tapentadol 57 None known-methadone-specific immunoassays have adequate sensitivity to detect methadone and/or EDDP in urine Buprenorphine Common targets Buprenorphine Norbuprenorphine (met)…”
Section: Opiatesmentioning
confidence: 99%
“…Poppy seed containing foods 1,2,18,48 , some fluoroquinolone antibiotics (levofloxacin 49 , ofloxacin 49 ), imipramine 46 , naltrexone 46 , naloxone 50 , rifampin/rifampicin 51 53 , verapamil 54 , verapamil metabolites 54 , quetiapine 55,56 , tapentadol 57 None known-methadone-specific immunoassays have adequate sensitivity to detect methadone and/or EDDP in urine Buprenorphine Common targets Buprenorphine Norbuprenorphine (met)…”
Section: Opiatesmentioning
confidence: 99%
“…Methadone-specific analysis techniques are therefore required for its detection, and immunoassays such as the DRI methadone assay (Microgenics Corp, Freemont, CA, USA) are commercially available for this opioid drug. Recently, tapentadol, a newer prescription analgesic, has been shown to react with the DRI methadone assay producing false positive results [73]. Although the cross-reactivity in the assay is low, it illustrates the need for confirmatory testing especially when the result does not fit with the clinical situation.…”
Section: Methadonementioning
confidence: 99%
“…Although we found no amphetamine cross-reaction with the immunoassay, another recent study has demonstrated cross-reactivity with a similar immunoassay for methadone. 7 …”
mentioning
confidence: 99%